Association of Peri-Implant Health Status With COVID-19 - Fatemah AlAhmari; Reghunathan S. Preethanath; Darshan Devang Divakar; Dena Ali (Elsevier, 2023)
ABSTRACT: Objective: The aim of this research was to evaluate peri-implant health status in patients infected with COVID-19 and control patients (individuals without COVID-19). Methods: This observational investigation was performed in adults with (test group) and without (control group) COVID-19 infection having at least 1 functional dental implant. Self-reported education status and daily frequency of toothbrushing and flossing was determined. A questionnaire was administered to record demographic data, brushing/flossing frequency, and education status. Periodontal examination comprised full-mouth assessment of clinical attachment loss (CAL), plaque index (PI), probing depth (PD), and gingival index (GI). Peri-implant PD, modified PI, and modified gingival index were recorded. Loss of marginal and crestal bone around teeth and implants was also measured. Significance level was established for P < .05. Results: Seventy-three (41 males) and 71 (44 males) individuals were included in the test and control groups, respectively. Average ages of patients and controls were 44.6 ± 5.2 and 40.1 ± 3.1 years, respectively. University-level education was attained by 52 (75.3%) and 50 (70.4%) individuals in the test and control groups, respectively. Seventy (95.9%) and 68 (95.7%) patients and controls were brushing twice a day. Once-daily interproximal flossing was reported by 44 (60.3%) and 48 (67.6%) individuals in test and control groups. All participants had healthy periodontal and peri-implant tissues. Conclusions: The study indicated that there are no short-term adverse effects on the peri-implant tissues due to acute COVID-19 infection, and further well-controlled longitudinal studies are needed to evaluate the long-term effect of the infection on these tissues.